A Study of Nursing Outcomes Indicators of Acute Stroke Patients in Community Hospitals - Chaikulab, Thapanee; Wisesrith, Wasinee (Journal of The Royal Thai Army Nurses, 2020)
This research is a descriptive research to determine the outcome indicators for acute stroke patients in community hospitals. And how to define the indicators is the researcher will review the related literature and use theoretical method as a preliminary indicator of the conceptual framework and the opinions of experts who have knowledge, ability and experience. The expert group consists have 21 persons, divided into 5 Nursing instructor and academic group, 7 nursing administrators, 6 Advance practice nurse and 3 Stroke specialist doctor. The data collection tool is the questionnaire about the indicators of nurses in acute stroke patients in community hospitals, 3 rounds include opened end questionnaires and rating scale questionnaires and showing the quartile range questionnaires and median for the expert to confirm the answer or change the answer Data analysis by using statistics to measure central tendency and interquartile range. The study found that the results of indicators for acute stroke patients in community hospitals include 7 domains, 41 indicators: 1) The safety of the nervous system and brain. 2) The access and efficiency of the period of receiving thrombolytic drugs. 3) The coordinating care and transfer to another hospital. 4) The satisfaction of patients and family in receiving services. 5) The psychological response of patients and family. 6) Discharge planning. 7) Continuing of care.